The Effect of Magnetic Letter-Based Play Activities on Early Literacy Skills of Children Aged 5-6 Years - Zuhroh Fajriati; Rusmayadi Rusmayadi; Fitriani Dzulfadhilah (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Early literacy skills are a critical foundation for children’s readiness to enter formal education. However, data show that Indonesia ranks 67th out of 81 countries in PISA 2022, indicating that literacy competency requires strengthening from the earliest stages of education. Initial observations revealed that of the 39 children in Group B, 5 had not recognized any letters at all, while 15 only recognized some letters; from this population, a purposive sample of 20 children exhibiting sub-optimal early literacy was selected and divided into an experimental group (n=10) and control group (n=10). This study aims to investigate (1) the description of magnetic letter media use, (2) children’s early literacy ability before and after treatment, and (3) the effect of play activities using magnetic letter media on early literacy skills. A quasi-experimental approach with a Non-Equivalent Control Group Design was employed. Data were collected through observation, tests, and documentation, then analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. Result showed that the experimental group’s mean score increased from 28.4 (pre-test) to 38.3 (post-test), a gain of 9,9 points, while the control group only increased by 2.6 points. The Wilcoxon test yielded a significance value of 0.005 (p < 0.05), confirming that play activities using magnetic letter media significantly enhance early literacy skills in children aged 5-6 years at Makassar of Islam Al-Abrar Kindergarten.